ANALISIS PERKEMBANGAN PEMBERIAN PRODUK KREDIT CEPAT DAN AMAN (KCA) PADA PT. PEGADAIAN (PERSERO) KANWIL V MANADO - Hurul Ain R. Lamampa; F.A.O. PELLENG; H. J. Sumampouw (Universitas Sam Ratulangi, 2016)
Abstract. The existence Pegadaian (Persero) is increasingly important and strategic in supporting policy implementation of government programs in economics and national development. This happens because a lot of people and SMEs who know exactly where Pawnshops are able to contribute both through its lending, with procedures (carrying the collateral) is easy. Another thing that can affect the Mortgage Loans in improving service provision Quickly and Safely (KCA) to the community is the provision of financing through loans faster and safer. The purpose of this study was to determine the analysis of the development of the provision of credit products quickly and safely (KCA) on PT. Pegadaian (Persero). Pawn is an acquired right person indebted on an item on his behalf, and that gives power to those who were indebted to take repayment of the item is precedence over those of other indebted; with the exception of charges for the auctioning of goods and which have been issued to save him after the goods were pawned. This type of research is qualitative research with quantitative approach forecasts. In the process of data collection using observation author. While the data used in the form of primary data and data analysis used sekunder.Teknik is a trend analysis. The above results can be summarized in 2014 to 2015 reached rise to 11%. Because Pegadaian a lot of money-expenditures for implementation from here can be explained, the imbalance between the loan money disbursed by the pawnshop with the gains of the money outstanding loans to customers. However Pegadaian continue to increase its lending to the public by lowering interest rates. KCA mortgage loans to the public and Pegadaian each year has increased from year to year. Increasing the provision of mortgage loans due to the many customers KCA. And can be expected in the future a more creative, innovative because of the many people who pawned the goods, then the employee should be conscientious Pegadaian performed the assessment of the pawned goods. Keywords: Quick Credit danAman (KCA), Development Lending.